Design procedure and digital control of a DCM flyback converter: component sizing and experimental validation - Nabil Abouchabana; Mohammed Benmiloud; Khaled Ameur; Aboubakeur Hadjaissa (Institute of Advanced Engineering and Science, 2026)
Flyback converters are widely used in low-power switch-mode power supplies (SMPS) due to their simple structure, galvanic isolation capability, and cost effectiveness. This paper presents a systematic design methodology and digital Proportional–Integral (PI) control implementation for a discontinuous conduc tion mode (DCM) flyback converter using a dSPACE 1104 control platform. The proposed approach integrates magnetic component sizing, semiconductor stress evaluation, and RCD snubber design into a unified workflow. A 30 W prototype operating at 30 kHz with an input range of 20–30 V and a regulated 12 V output was developed and experimentally validated. The digital PI con troller was tuned using Takahashi’s method to ensure stable voltage regulation. Experimental results demonstrate proper DCM operation and stable output regulation under input voltage variation (20–30 V), load variation (48 Ω–12 Ω), and reference changes (10–14 V). The measured efficiency exceeded 90% at nominal operating conditions. The results confirm the effectiveness of the proposed design methodology for low-power isolated DC–DC applications.